Risk Factors of Cholera Transmission in Al Hudaydah, Yemen: Case-Control Study - Abdulqawi Mohammed Qaserah; Mohammed Abdullah Al Amad; Abdulwahed Abduljabbar Al Serouri; Yousef Saleh Khader (JMIR Publications, 2021)
BackgroundYemen has recently faced the largest cholera outbreak in the world, which started at the end of 2016. By the end of 2017, the cumulative reported cases from all governorates reached 777,229 with 2134 deaths. Al Hudaydah was one of the most strongly affected areas, with 88,741 (18%) cases and 244 (12%) deaths reported. ObjectiveThe aim of this study was to determine the risk factors associated with cholera transmission in Al Hudaydah city, Yemen. MethodsFrom December 1, 2017 to January 10, 2018, a total of 104 patients with cholera (57 women and 47 men) who presented at cholera treatment centers in Al Hudaydah city with three or more watery stools in a 24-hour period and with moderate or severe dehydration were identified for inclusion in this study. Each case was matched by age and gender with two controls who were living in the neighboring house. A semistructured questionnaire was used to collect data on behavioral and environmental risk factors such as drinking water from public wells, storing water in containers, consumption of unwashed vegetables or fruits, and sharing a toilet. ResultsThe median age of the cases and controls was 20 years (range 5-80) and 23 years (range 5-85), respectively. Only 6% of cases and 4% of controls were employed. Multivariate analysis showed that eating unwashed vegetables or fruits (odds ratio [OR] 7.0, 95% CI 1.6-30.6, P=.01), storing water in containers (OR 3.0, 95% CI 1.3-7.3, P=.01), drinking water from a public well (OR 2.5, 95% CI 1.1-5.7, P=.02), and using a public toilet (OR 5.2, 95% CI 1.1-24.4, P=.04) were significantly associated with cholera infection risk. ConclusionsThe cholera transmission risk factors in Al Hudaydah city were related to water and sanitation hygiene. Therefore, increasing awareness of the population on the importance of water chlorination, and washing fruits and vegetables through a health education campaign is strongly recommended.